Analisa Dan Evaluasi Penggunaan SCADA Pada Keandalan Sistem Distribusi PT. PLN (Persero) Area Pembagi Distribusi Riau Dan Kepulauan Riau - Illahi, Hayatul; M, Noveri L (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
One parameter of reliabilities from The Electrical Power Distribution System is the continuity of electrical power supply to the consumers. Therefore, it is needed a system that can monitor and control the performance of the distribution system in real-time and based on computers. The system which perform such these jobs is Supervisory Control and Data Acquisition (SCADA) system. The Distribution System has been integrated with SCADA can minimize the time disturbances that has effect to the reliability index of Electrical Power Distribution System. Use reability indexin this research refers to index of Electrical Power Distribution System that is the value of System Average Interruption Duration Index (SAIDI). This reliability index associated with the member disturbancesan and long disruption of the Distribution System. Index of Distribution System reliability of PT. PLN (Persero) APD Riau and Riau Islands has increased after the integration with SCADA systems. In this case percentage from reliability index Distribution System increase based on the analysis and calculation of SAIDI index value is 41.62%.Keywords: Distribution System, Reliability, SAIDI, SCADA, Time Disturbance